DESIGN CONSIDERATIONS FOR TRAWL WINCHES - VELU, M (Fishery Technology, 2016)
For efficient functioning of a trawl winch it is essential thmall component parts should be designed carefully takinginto consideration all the relevant factors such as quantum andtype of load each component is subjected to, amount of maintenanceit will receive during actutal operation, type of driv.:: for the winch etc.Based on the practices adopted at the Central Institute OfFisheries Technology certain guide lines are proposed in this p::tperfor designing of trawl winches.